PERBEDAAN KECERDASAN EMOSI ANTARA REMAJA YANG MENGIKUTI AKTIVITAS BERMAIN GAMELAN DENGAN REMAJA YANG TIDAK MENGIKUTI AKTIVITAS BERMAIN GAMELAN - Narulia Asrandini; Kondang Budiyani (UIN Sunan Kalijaga, 2013)
The research aimed to explore emotional quotion differences at youth both who play gamelan and do not at Vocational High School Kasihan I Bantul.The result of analysis with sample t-tes independent showed that there is different between coefcient t value as 3,003 (p<001). Furthur, there is different between emotional qoution at youth who play gamelan activity with score mean (M= 162,58) is higher than youth who do not play gamelan activity.